A Generalized Equatorial Model for the Accelerating Solar Wind. Issue 2 (26th February 2018) - Tasnim, S.; Cairns, Iver H.; Wheatland, M. S.
Abstract: A new theoretical model for the solar wind is developed that includes the wind's acceleration, conservation of angular momentum, deviations from corotation, and nonradial velocity and magnetic field components from an inner boundary (corresponding to the onset of the solar wind) to beyond 1 AU. The model uses a solution of the time‐steady isothermal equation of motion to describe the acceleration and analytically predicts the Alfvénic critical radius. We fit the model to near‐Earth observations of the Wind spacecraft during the solar rotation period of 1–27 August 2010. The resulting data‐driven model demonstrates the existence of noncorotating, nonradial flows and fields from the inner boundary ( r = r s ) outward and predicts the magnetic fieldB = ( B r, B ϕ ), velocityv = ( v r, v ϕ ), and density n ( r, ϕ, t ), which vary with heliocentric distance r, heliolatitude ϕ, and time t in a Sun‐centered standard inertial plane. The description applies formally only in the equatorial plane. In a frame corotating with the Sun, the transformed velocity v ′ and a field B ′ are not parallel, resulting in an electric field with a component E z ′ along the z  axis. The resulting E ′ × B ′ = E ′ × B drift lies in the equatorial plane, while the∇ B and curvature drifts are out of the plane. Together these may lead to enhanced scattering/heating of sufficiently energetic particles. The model predicts that deviations δ v ϕ from corotation at the inner boundary are common, with δ v ϕ ( r s, ϕs, t s ) comparable to the transverse velocities due to granulation and supergranulation motions. Abrupt changes in δ v ϕ ( r s, ϕs, t s ) are interpreted in terms of converging and diverging flows at the cell boundaries and centers, respectively. Large‐scale variations in the predicted angular momentum demonstrate that the solar wind can drive vorticity and turbulence from near the Sun to 1 AU and beyond. Key Points: A generalized theoretical model that includes the wind's acceleration and allows intrinsic velocities and magnetic fields is presented This model allows a deviation from corotation The intrinsic nonradial magnetic fields and velocities are explained in terms of motion of the granulation and supergranulation cells